(untitled) - Robin J Wilson (London, 1996)
The contents of this book may be divided into four parts. The first of these provides a basic foundation course, containing definitions and examples of graphs, connectedness, Eulerian and Hamiltonian path and cycles, and trees. The second part is on planarity and colouring. The third part deals with the theory of directed graphs and with transversal theory, with applications to critical path analysis, Markov chains and network flows. The book ends with a chapter on matroids, which is used to consolidate some of the material from earlier chapters
Keywords: graph theory